'' Development of an inclusive education system in preschool education '' - Saidova Shahlo Akmalovna (Genius Journals, 2022)
In this article, the work being done to educate children with disabilities, the new education system introduced in our country, ie the improvement of the inclusive education system, and the introduction of this education system in preschool education was mentioned.
Keywords: inclusive education; wheelchair; education; teaching methods